Downregulation of DUSP9 Promotes Tumor Progression and Contributes to Poor Prognosis in Human Colorectal Cancer - Qiu, Zhaoyan; Liang, Ning; Huang, Qian; Sun, Tao; Xue, Hongyuan; Xie, Tianyu; Wang, Xinxin; Wang, Qian (Frontiers in Oncology, 2020)
Background Dual-specificity phosphatase 9 (DUSP9) belongs to the dual-specificity protein phosphatase subfamily. Recently, increasing attention has been paid on the role of DUSP9 in a variety of cancers. However, its functional role in tumor development is still unclear, especially in colorectal cancer (CRC). Methods The functional role of DUSP9 in inhibiting the progression of CRC was verified using colony formation assay, wound healing assay, nude mice xenograft model, and et al. RNA-seq was performed to assess the gene expression profiling in SW480 cells with DUSP9 stable knockdown and shControl cells. Bisulfite sequencing (BSE) was performed to reveal methylation status of CpG island in promoter of DUSP9. Results DUSP9 was significantly down regulated in tumor tissues compared with peritumor tissues. Mechanistically, the high methylation status of CpG island in promoter of DUSP9 may lead to the down-regulation of DUSP9 in CRC. Clinically, low DUSP9 expression in CRC was closely associated with depth of invasion, metastasis (TNM) stage and poor survival, indicating that DUSP9 may be involved in the progression of CRC. Functional study revealed that DUSP9 inhibited proliferation, migration, invasion and epithelial–mesenchymal transition of CRC cells both in vitro and in vivo. Transcriptome profiling studies revealed Erk signaling was involved in the tumor progression mediated by DUSP9 silencing, which is confirmed by cell experiments and clinical tissue sample staining analysis. Conclusion Our findings demonstrate that DUSP9 plays a critical role in the progression of CRC and therapeutic intervention to increase the expression or activity of DUSP9 may be a potential target for CRC treatment in the future.